1990
DOI: 10.1080/00288233.1990.10428424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cobalt application on the cobalt status of pastures 3. Comparison of chelate and sulphate as cobalt sources for topdressing deficient pastures

Abstract: Cobalt chelate (Co EDTA) and cobalt sulphate(CoS0 4 ) , appliedin liquidand solidforms, were compared as sources of cobalt (Co) for topdressing pastureata sitelocatedwithinapaddock~e r~grazing lambs r~sponded to vitamin B 12 mjecuon.The two matenals were equallyeffective in increasing pasture Co concentration but the effects from both lasted only about 100 days. Rate of application of bothmaterialsaffectedthemaximum pastureCoconcentration obtainedbutdidnotgreatly influencethe duration of the response.There was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 10 publications
1
16
1
Order By: Relevance
“…This is also true for fertilisation efforts to increase Co concentrations in pasture plants. An examination of this literature indicates that the response of plant Co concentrations to Co fertilisation, as is the case for 'native' Co, is mixed and is dependent upon a number of factors including the rate, and delivery, of fertilisation (McLaren and Williams 1981;Nicolls and Honeysett 1964;Sherrell 1990a), the chemical and physical form of the Co fertiliser (Klessa et al 1989;McLaren and Williams 1981;Sherrell 1990b), the plant species (Klessa et al 1989;McLaren and Williams 1981;Sherrell 1990a), and reactions occurring between the added Co with soil components (Adams et al 1969;Klessa et al 1989;Li et al 2004;McLaren et al 1987;Nicolls and Honeysett 1964;Rosbrook et al 1992;Sherrell et al 1990). Rosbrook et al (1992) have reported that Co concentrations in Lupinus angustifolius L. did not significantly increase in 11 Queensland soils when applications of solid CoSO 4 between 0.03 and 0.4 mg Co/kg were added.…”
Section: Anthropogenic Co (Fertilizers and Soil Contamination)mentioning
confidence: 98%
See 1 more Smart Citation
“…This is also true for fertilisation efforts to increase Co concentrations in pasture plants. An examination of this literature indicates that the response of plant Co concentrations to Co fertilisation, as is the case for 'native' Co, is mixed and is dependent upon a number of factors including the rate, and delivery, of fertilisation (McLaren and Williams 1981;Nicolls and Honeysett 1964;Sherrell 1990a), the chemical and physical form of the Co fertiliser (Klessa et al 1989;McLaren and Williams 1981;Sherrell 1990b), the plant species (Klessa et al 1989;McLaren and Williams 1981;Sherrell 1990a), and reactions occurring between the added Co with soil components (Adams et al 1969;Klessa et al 1989;Li et al 2004;McLaren et al 1987;Nicolls and Honeysett 1964;Rosbrook et al 1992;Sherrell et al 1990). Rosbrook et al (1992) have reported that Co concentrations in Lupinus angustifolius L. did not significantly increase in 11 Queensland soils when applications of solid CoSO 4 between 0.03 and 0.4 mg Co/kg were added.…”
Section: Anthropogenic Co (Fertilizers and Soil Contamination)mentioning
confidence: 98%
“…In fact, plant Co concentrations are typically <10 mg/kg and, more often than not, <1 mg/kg (Adams and Honeysett 1964;Adams et al 1969;Gille and Graham 1971;Gupta 1993;Klessa et al 1989;Li et al 2004;McLaren et al 1987;McLaren and Williams 1981;Nicolls and Honeysett 1964;Paterson et al 1991;Price et al 1955;Rosbrook et al 1992;Sherrell et al 1990). For comparative purposes, the threshold deficiency concentration of Co in pastures for sheep and cattle grazing has been identified as 0.05-0.1 mg/kg (Gupta 1993;Klessa et al 1989;Sherrell 1990b;Sherrell et al 1990). Despite the fact that higher plants may control, to a large degree, Co uptake, soil parameters are also likely to be involved in the seven orders of magnitude difference in plant Co concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Trace element-amended fertilisers can increase concentrations of Co, Se, and Cu in pasture up to 10-fold for 4-12 months (Watkinson 1983;Sherrell 1984;Grace et al 1998). The response depends on factors such as rate of application, botanical composition, and soil type.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these crops are grown in areas where Co, Se, and Cu deficiencies have been observed in grazing animals (Grace 1994). One approach to increase the trace element intakes and prevent deficiencies in grazing livestock is to topdress pastures with Co-, Se-, and Cu-amended fertilisers (Watkinson 1983;Sherrell 1984;Grace et al 1998). The effect of using amended fertilisers on brassica crops to increase their Co, Se, and Cu concentrations has not been well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Often, CoSO 4 applied with superphosphate topdressing in spring is unable to maintain herbage Co concentrations at adequate levels for grazing animals in the subsequent months. Sherrell (1990c) proposed the use of a slow-release source of Co to overcome the pattern of immediate high pasture Co concentrations followed by rapid decline to deficient levels. However, initial field evaluation of slow-release Co fertiliser prills based on cobalt hydroxide (Co(OH) 2 ) showed that they were ineffective (M. B. O'Connor pers.…”
Section: Introductionmentioning
confidence: 99%